Claulansine F promotes neuritogenesis in PC12 cells via the ERK signaling pathway - Ma Yin-zhong; Ning Na; He Wen-bin; Li Jing-wei; Hu Jin-feng; Chu Shi-feng; Chen Nai-hong (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of Claulansine F (Clau F), a carbazole alkaloid isolated from the stem of Clausena lansium (Lour) Skeels, on neuritogenesis of PC12 cells, and to elucidate the mechanism of action. Methods: Neuritogenesis of PC12 cells was quantified under an inverted microscope. Expression of the neurite outgrowth marker GAP-43 was detected using immunofluorescence. GAP-43 transcription was measured using RT-PCR. Cell viability was evaluated with MTT assay. The levels of phosphor-ERK1/2, phosphor-CREB, phosphor-AKT and acetylate-p53 in the cells were examined using Western blotting analyses. Results: Clau F (10–100 μmol/L) significantly increased the percentage of PC12 cells bearing neurites. Clau F markedly increased the expression of GAP-43 in the cells. The efficiency of Clau F (10 μmol/L) in increasing neuritogenesis and GAP-43 expression was comparable to that of nerve growth factor (50 ng/mL). In addition, Clau F completely blocked the proliferation of PC12 cells within 7 d of incubation, whereas it did not cause cell death in cultured rat cortical neurons. Treatment of PC12 cells with Clau F activated both ERK and AKT signaling pathways. Co-treatment of PC12 cells with the specific ERK inhibitor PD98059, but not the specific PI3K inhibitor LY294002, blocked Clau F-induced neuritogenesis and GAP-43 upregulation. Conclusion: Clau F promotes neuritogenesis in PC12 cells specifically via activation of the ERK signaling pathway.